Changes in Selected Quality Characteristics, Polyphenoloxidase Activity and Protein Profile in Relation to Ascorbic Acid Treatment of Minimally Processed Carambola (Averrhoa Carambola L.) - Ding, Phebe (1999)
A study on the changes in selected quality characteristics, polyphenoloxidase activity (PPO) and protein profile in relation to ascorbic acid treatment of minimally processed carambola was conducted. 'B10' carambola at maturity stages 3 and 4 were packed in boxes and precooled at 10˚C in a cold room. After 24 hrs the fruits were washed, the edges trimmed-off, sliced transversely into l-cm-thick slices and dipped in 0, 15 and 30 mg.L-1 of 4˚C ascorbic acid solution for 2 min. The slices were dried using tissue paper, placed on TP2 polystyrene foam tray, cling-wrapped and stored at 7˚C for 0, 3 and 5 days. The experiment was conducted using a randomized complete block design (RCBD) with a factorial arrangement of treatments (3 ascorbic acid x 2 maturity index x 3 storage days) and four replications. Data from measurements of the skin colour (L*, C* and h˚), flesh finnness, soluble solids concentration, vitamin C content, pH, sensory evaluation, browning degree and PPO activity were analyzed using analysis of variance (ANOYA) and differences within each factor were determined by Least Significant Difference (LSD).